2019
DOI: 10.1101/824052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More than DNA methylation: does pleiotropy drive the complex pattern of evolution ofDnmt1?

Abstract: 9DNA methylation is an important chromatin modification that can stably alter gene expression in 10 cells and maintain genome integrity in plants and vertebrates. The function of DNA methylation 11 outside of these well-studied systems, however, is unclear. Insects, in particular, represent an 12 understudied group. Variation in the level of DNA methylation and gains and losses in the 13 maintenance methyltransferase, DNMT1, across the insect tree of life suggests that there is much we 14don't understand about… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Thus, the phenotypic similarity between Dnmt1knockdown and Vasa knockdown testes in O. faciatus support the hypothesis that Dnmt1 may be required for the successful initiation and completion of meiosis in spermatocytes. More work remains to determine exactly what stage of sperm development is impacted by the decrease in Dnmt1 expression.The phenotype of knockdown of Dnmt1 is exacerbated when knockdown occurs prior to the stage of testis development when meiosis occurs, as was observed in female O. fasciatus(Amukamara et al 2020). One interpretation of this result is that Dnmt1 is required for successful progression through meiosis.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, the phenotypic similarity between Dnmt1knockdown and Vasa knockdown testes in O. faciatus support the hypothesis that Dnmt1 may be required for the successful initiation and completion of meiosis in spermatocytes. More work remains to determine exactly what stage of sperm development is impacted by the decrease in Dnmt1 expression.The phenotype of knockdown of Dnmt1 is exacerbated when knockdown occurs prior to the stage of testis development when meiosis occurs, as was observed in female O. fasciatus(Amukamara et al 2020). One interpretation of this result is that Dnmt1 is required for successful progression through meiosis.…”
mentioning
confidence: 75%
“…We also collected virgin males on the day of adult emergence and after sexual maturation at 7 days post-adult-emergence. We collected and tested these samples at the same time as the data reported for females (Amukamara et al 2020). Because 2nd and 3rd instar nymphs cannot be reliably sexed, the data presented here is the same as that presented in the previous publication.…”
Section: Developmental Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knocking out reproductive capacity is attractive because B. tabaci reproduction can be knocked out at several stages. Potential genes include those involved in gamete viability such as Boule , Vasa , or DNA methyltransferase 1 ( Dnmt1 ) [ 86 , 87 , 88 , 89 ]. The latter suggestion is a good example of the importance of understanding specific gene function.…”
Section: Selecting Suitable Targets Based On Pathway Involvementmentioning
confidence: 99%
“…However, methylation in insects does not appear to be universal, and some species such as the genetic model species D. melanogaster and Tribolium confusum lack Dmnt1 altogether [ 90 ]. Yet in Oncopeltus fasciatus , a hemipteran, co-authors have shown through RNAi knockdown that Dnmt1 has an essential function in gamete production in both males and females and that the silencing of Dnmt1 results in sterility without causing mortality or disrupting somatic tissue [ 86 , 87 ]. The Dnmt1 gene sequence has been identified in B. tabaci and successfully knocked down using RNAi [ 91 ].…”
Section: Selecting Suitable Targets Based On Pathway Involvementmentioning
confidence: 99%